'A war against truth' - understanding the fake news controversy. Issue 2 (3rd May 2020) - Monsees, Linda
ABSTRACT: Fake News, dis- and misinformation campaigns are a core concern for current democratic societies. Whereas most academic interventions have focused on the epistemological and political implication, this paper provides an empirically informed analysis of the fake news controversies. Through an empirical analysis of the German fake news controversy, this paper advances two points: It first gives insights into how the fake news controversy unfolded in Germany. The article shows how multiple issues such as racism, social media and the geopolitical threat of Russia were bound together. Second, on a conceptual level, this article argues for analysing security controversies as a valuable tool to understand new security anxieties. In the context of fake news, studying the controversy reveals how anxieties concerning fake news are produced and reinforced by linking them through a multiplicity of issues. (In)security emerges in controversies where threats in and through new media are linked with the problem of fake news. As a result, 'fake news' becomes part of the broader security landscape of contemporary societies.